MANAJEMEN SEKOLAH BERBASIS MODERASI BERAGAMA UNTUK MEWUJUDKAN PENDIDIKAN TOLERANSI DI INDONESIA - Saekan Muchith, Mukhamad (Penerbit Lafadz Jaya, 2025)
Religious moderation-based school management is a strategic approach to creating an inclusive, harmonious, and equitable educational environment. This approach focuses on developing values of tolerance, balance, and respect for religious diversity within the school community. By integrating the principles of religious moderation, schools are expected to become a space for constructive interreligious and intercultural understanding. This study assesses the implementation of religious moderation-based management through a literature review and analysis of socio-religious phenomena in Indonesia. The results show that this approach is able to reduce the potential for conflict, increase collaboration between school members, and strengthen multicultural character education. Important strategies in implementing this management include developing an inclusive curriculum, training teachers on religious diversity, and establishing a leadership structure that reflects plurality. The positive impacts of implementing religious moderation-based school management include increasing students' tolerance and creating a more cohesive school climate. This article concludes that the implementation of religious moderation-based management has great potential to foster tolerance in Indonesia's pluralistic society.